Transformasi Digital Marketing dalam Peningkatan Loyalitas Pasien di Rumah Sakit: Studi Eksperimen Interaktif Berbasis AI Chatbot - Puspa Widiyawati; Ria Anggraeni Lubis; Orieza Sativa Novitaloka (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation has brought profound changes to healthcare marketing strategies, particularly in building patient loyalty through more personalized, responsive, and technology-driven communications. This study focuses on the contribution of AI chatbots as part of a hospital's digital marketing strategy in building patient loyalty. The approach used was descriptive qualitative with a phenomenological method, where data was obtained through in-depth interviews and participant observation of patients who had used chatbot services. Thematic analysis identified five key themes: ease of access to information, service personalization, sense of security and trust, limited empathy, and positive impact on service reuse intentions. The results show that AI chatbots function effectively as an initial communication medium capable of increasing patient trust and emotional engagement, although they have not completely replaced human communication, especially in situations requiring high empathy. These findings indicate the need for a hybrid strategy that combines technological efficiency with human involvement, so that communication remains adaptive and effective. Furthermore, the development of Natural Language Processing-based chatbots is crucial for increasing the sensitivity, relevance, and quality of interactions. Conceptually, this study enriches the understanding of digital marketing in the healthcare sector, and practically provides recommendations for hospitals in strengthening patient loyalty strategies amidst the increasingly rapid flow of digital transformation.